STUDI TRANSFORMATOR PADA GARDU INDUK PANAKKUKANG PERUSAHAAN LISTRIK NEGARA WILAYAH III - Abdul Hafid; Debiana Debiana (Fakultas Teknik Universitas Muhammadiyah Makassar, 2019)
The operation failure of one of the main substation equipment, resulting in a number of end-users of electricity will be impaired. Maintenance on major equipment substation needs to be done to prevent damage and disruption as early as possible, and can extend the life of the equipment. Thus, the system of maintenance of equipment at a substation needs to be maintained and improved, especially on equipment - equipment that is essential for channel function and securing of a power interruption.